DESIGN AND DEVELOPMENT OF MOTORIZED ACCIDENT PREVENTION TOOL USING ULTRASONIC SENSOR BASED ON ARDUINO UNO - Sembodo, Budi Prijo; Rama Oktawiaci, Oebet (Tibuana, 2019)
Ultrasonic proximity sensor with a bluetooth headset is a tool that aims to minimize the number of accidents that often occur on the highway. With the aim of the importance of a tool that supports safety in carrying out activities in our daily lives, we drive. Ultrasonic proximity sensor with bluetooth headset has advantages in usage such as comfort, safety, and practicality. The method used in making this tool after finding the root of the problems that have been faced becomes an inspiration that is developed into a solution as outlined in a draft safety tool. For the development of this tool, it needs to be tested or monitored on the highway that is prone to accidents as a tool to improve this tool to function as a security tool. Improvement of this tool also requires a short time, in achieving improvement becomes a tool that can remind when driving. If our vehicle uses this tool, the road is prone to frequent accidents, being controlled by the distance that will be reminded through the sound coming out of the bluetooth headset.